The effects of dental implant macrodesign on the success of prosthetic replacement - Andrey N. Nikolaenko; Mikhail A. Postnikov; Nikolay V. Popov; Alexander P. Borisov; Anastasia A. Kiiko (Клиническая практика)
Currently dental implantation is widely used in the areas of denture defects during the orthopedic rehabilitation of the patients. The clinical success of the implantation-related prosthetic replacement depends on multiple factors, including the macrodesign of the implant (the specific features of its structure: the shape, the characteristics and the number of thread turns). However, there are not so many comparative clinical trials exploring the effects of the main characteristics of the implant on the success of prosthetic procedures. For the practical dentist, the problem of selecting the implant system remains topical, which is why the proposed review is focused on the effects of the dental implant macrodesign on the success of implantation. The search of publications was arranged in the PubMed and eLibrary search engines using the “dental implant”, “dental implant macro-design”, “number of dental implant turns” and “implant thread characteristics” search enquiries with focusing on the research works evaluating the effects of the main characteristics of the implant in terms of primary stability and osteointegration. Various geometric parameters of the implant were analyzed, such as the shape, the length, the diameter and the thread characteristics, with further evaluating their significance for optimal tension distribution, as well as the effects on bone remodeling during the process of osteointegration. The successful implantation is being achieved by synergetic combination of numerous factors. The majority of investigators adhere to the opinion that implants shall be selected individually for each specific case with taking into consideration the local and general factors. However, the characteristics of the implant thread and the number of its thread turns improve the primary stability and represent a prerequisite for successful osteointegration. The choice of implant thread construction plays an important role for a treatment result. It was shown that the macrodesign of the implant, specifically its shape (cone), its length and diameter, higher thread width and depth, lesser thread pitch and higher numbers of thread turns influence the primary stability. Specifically these characteristics, according to our opinion, assure the success of dental implantation.